2022
DOI: 10.3390/su14148764
|View full text |Cite
|
Sign up to set email alerts
|

Use of Metagenomic Whole Genome Shotgun Sequencing Data in Taxonomic Assignment of Dipterygium glaucum Rhizosphere and Surrounding Bulk Soil Microbiomes, and Their Response to Watering

Abstract: The metagenomic whole genome shotgun sequencing (mWGS) approach was used to detect signatures of the rhizosphere microbiomes of Dipterygium glaucum and surrounding bulk soil microbiomes, and to detect differential microbial responses due to watering. Preliminary results reflect the reliability of the experiment and the rationality of grouping microbiomes. Based on the abundance of non-redundant genes, bacterial genomes showed the highest level, followed by Archaeal and Eukaryotic genomes, then, the least abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…We hypothesize that the small diameter of our pots (6.4 cm) did not allow for sufficient coring distance from plant roots to make this distinction as the roots largely filled the available space. This finding challenges a common working definition of rhizosphere soil as that which is specifically attached to roots (Chaparro et al, 2014;Zhu et al, 2020;Shami et al, 2022). Kuzyakov and Razavi (2019) reviewed the temporal dynamics and spatial stationarity of plant rhizospheres and found that the rhizosphere generally extends 0.5-4 mm from plant roots.…”
Section: Insights On Inter-kingdom Associations Via Network Analysismentioning
confidence: 95%
“…We hypothesize that the small diameter of our pots (6.4 cm) did not allow for sufficient coring distance from plant roots to make this distinction as the roots largely filled the available space. This finding challenges a common working definition of rhizosphere soil as that which is specifically attached to roots (Chaparro et al, 2014;Zhu et al, 2020;Shami et al, 2022). Kuzyakov and Razavi (2019) reviewed the temporal dynamics and spatial stationarity of plant rhizospheres and found that the rhizosphere generally extends 0.5-4 mm from plant roots.…”
Section: Insights On Inter-kingdom Associations Via Network Analysismentioning
confidence: 95%
“… Citrus rhizosphere [ 102 ] Rhizophagus , Burkholderia , Trichoderma , Fusarium , Ochrobactrum phage POA1180 , Blastococcus , Microvirga , Nocardioides , Geodermatophilus , Belnapia , Solirubrobacter , Arthrobacter , Mycobacterium phage Edugator , and Mycobacterium phage Kratio Not identified. Cleome pallida (Desert plant) rhizosphere [ 103 ] Kaistobacter and Rubrobacter Bacillus Nocardioides , Cellulomonas , Skermanella , Methylobacterium , Modestobacter and Aeromicrobium , Rhizobiales , Kaistobacter , Rubrobacter or Bacillus Metabolism of carbohydrate (especially C degradation) and membrane transporters. Carbohydrate degradation metabolism, carbohydrate synthesis, and its related energy metabolism.…”
Section: Metagenomics: An Overviewmentioning
confidence: 99%